Reduced pupillary reward sensitivity in Parkinson’s disease - Manohar, S; Husain, M (Nature Publishing Group, 2015)
Abnormalities in reward processing may be a critical part of understanding non-motor manifestations of PD. Dysfunction in dopaminergic pathways, which signal upcoming rewards, might result in altered motivation by incentives. To examine this proposal, we studied sixteen patients with PD, both ON and OFF their normal dopaminergic medication, comparing them to healthy controls. Participants performed a speeded saccade task to obtain monetary rewards Crucially, we manipulated the reward available from trial to trial, by presenting an auditory incentive pre-cue before each saccade. The effects of incentives on pupil dilatation (an index of autonomic response) were measured. Individuals with PD showed diminished autonomic reward effects, compared to age-matched controls. When tested ON medication, pupil responses to reward increased, demonstrating that dopaminergic drugs can restore reward sensitivity. These findings reveal blunted autonomic responses to incentives in PD, which can be modulated by dopaminergic drugs.